Food Preferences and Nutrition in Rural Bangladesh - Pitt, Mark M. (The Review of Economics and Statistics, 1983)
T HE dietary choice of households near subsistence levels of nutrient intake is one of obvious policy importance. In many countries, such as Bangladesh, national goals are set in terms of nutritional intake and there is heavy intervention in the markets for foods. However, little is known about the manner in which food preferences vary with food expenditure and nutrient intake. The design of efficient programs to aid nutritionally deficient households in attaining minimal levels of nutrient intake requires information on all ownand cross-price elasticities for both target and non-target groups. The net effect of a food price subsidy on the consumption of food nutrients cannot be predicted without knowledge of the complete elasticity matrix. Results presented below demonstrate that substitution effects can be so strong that the subsidization of certain foods quite often reduces nutrient consumption. In this study, demand equations for nine foods which allow for extremely flexible consumer price response are estimated from the individual budgets of 5,750 rural Bangladeshi households. Estimation at the household level is preferred because it more readily permits the incorporation of household composition variables into the demand analysis, such as household size, occupation and employment status, that are typically lost in aggregation. There is also a greater range and variation in expenditure levels than found in grouped data. This is of particular importance in the study of nutritional well-being as it is the poorest households which are of special interest. Moreover, the household sample provides sufficient degrees of freedom to estimate a simple varying parameter model which requires the estimation of 270 parameters. Previous econometric analysis of income-class specific dietary choice has been limited and not altogether satisfactory. Pinstrup-Anderson, de Londono and Hoover (1976) estimated complete sets of price elasticities for different income strata using Frisch's scheme in order to study the impact of changes in relative prices on nutrient consumption. Their results are suspect because of the assumption of want independence necessary for this methodology to be valid. Alderman and Timmer (1980), who were also concerned with studying the relationship between food price policy and nutrient intake by income classes, econometrically estimated separate price coefficients for each income group by including slope dummy variables in their demand equations for rice and cassava in Indonesia. The inclusion of these dummy variables revealed surprisingly large differences in compensated price response across income groups. Although their results support the notion that poorer households respond differently to prices than the rich, the limitations of their data constrained them to consider only two foods and to specify changes in price response which are discontinuous with respect to income. I The formulation and estimation of the food demand equations is discussed in section II below. Section III presents the results of the estimation and discusses the nutritional implications of movements in relative food prices and other exogenous variables. Section IV summarizes our findings.